Prolapsed Lumbar Intervertebral Disease (PLID) Treatment in Acupuncture- A Case Study at Suoxi Acupuncture Hospital in Bangladesh - SM. Shahidul Islam; Hui Hui Li; Sabina Yasmin (Asian Journal of Medical Radiological Research, 2023)
Background: Low back pain and sciatica are very prevalent medical complaints. As a consequence of these adjustments, fewer hours will be worked and less of a toll will be taken on the national economy. A complete medical checkup is required before starting any kind of therapy for these people. Inadequate medical or surgical therapy may exacerbate symptoms, increasing the likelihood of this occurring. This research aims to learn whether and how acupuncture may improve standard PLID care. Subjects and Methods: This inquiry took place at Suoxi Hospital, Shaan Tower, Chamelibag, Shantinagar, Dhaka, Bangladesh. A 55-year-old male patient has been complaining of lower back discomfort for the last ten years. It had been seven years since he had found relief from the pain in his lower back, but now he was pain-free. The results of this research suggest that acupuncture may be helpful for those with PLID.